(untitled) (Journal of Parents and Teachers, 2026)
Tenderness is a feeling and an attitude that can transform everyday life into a unique experience. It is expressed through gestures, words, caresses and attention, although there are various obstacles that hinder its manifestation. By expressing it, we generate well-being for ourselves and others, which strengthens family and social bonds.